Overview of the Mechanisms of Action of Selected Bisphenols and Perfluoroalkyl Chemicals on the Male Reproductive Axes - Ješeta, Michal; Navrátilová, Jana; Franzová, Kateřina; Fialková, Sandra; Kempisty, Bartozs; Ventruba, Pavel; Žáková, Jana; Crha, Igor (Frontiers in Genetics, 2021)
Male fertility has been deteriorating worldwide for considerable time, with the greatest deterioration recorded mainly in the U.S., Europe countries, and Australia. That is, especially in countries where an abundance of chemicals called endocrine disruptors has repeatedly been reported, both in the environment and in human matrices. Human exposure to persistent and non-persistent chemicals is ubiquitous and associated with endocrine-disrupting effects. This group of endocrine disrupting chemicals (EDC) can act as agonists or antagonists of hormone receptors and can thus significantly affect a number of physiological processes. It can even negatively affect human reproduction with an impact on the development of gonads and gametogenesis, fertilization, and the subsequent development of embryos. The negative effects of endocrine disruptors on sperm gametogenesis and male fertility in general have been investigated and repeatedly demonstrated in experimental and epidemiological studies. Male reproduction is affected by endocrine disruptors via their effect on testicular development, impact on estrogen and androgen receptors, potential epigenetic effect, production of reactive oxygen species or direct effect on spermatozoa and other cells of testicular tissue. Emerging scientific evidence suggests that the increasing incidence of male infertility is associated with the exposure to persistent and non-persistent endocrine-disrupting chemicals such as bisphenols and perfluoroalkyl chemicals (PFAS). These chemicals may impact men's fertility through various mechanisms. This study provides an overview of the mechanisms of action common to persistent (PFAS) and nonpersistent (bisphenols) EDC on male fertility.